1997
DOI: 10.1093/humrep/12.2.373
|View full text |Cite
|
Sign up to set email alerts
|

Dioxin concentrations in women with endometriosis

Abstract: The concentrations of the enviromental pollutant 2,3,7,8-tetrachlorodibenzo-p-dioxin were measured in the blood of 44 infertile women with endometriosis (study group), and in 35 age-matched women with tubal infertility (control group). Eight women with endometriosis (18%) were dioxin positive as compared to one woman (3%) in the controls (P = 0.04). Although the concentrations of dioxin did not seem to be directly correlated with the severity of endometriosis, these observations contribute to the accumulating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
67
0
4

Year Published

1997
1997
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 169 publications
(77 citation statements)
references
References 10 publications
3
67
0
4
Order By: Relevance
“…For example, elevated blood levels of PCBs were discovered in Belgian women who suffer from endometriosis (17). A recent study in Israel has also demonstrated an association between endometriosis and elevated 2,3,7,8-TCDD levels (18).…”
Section: Methodsmentioning
confidence: 99%
“…For example, elevated blood levels of PCBs were discovered in Belgian women who suffer from endometriosis (17). A recent study in Israel has also demonstrated an association between endometriosis and elevated 2,3,7,8-TCDD levels (18).…”
Section: Methodsmentioning
confidence: 99%
“…Among these factors, dioxin is a prominent candidate for involvement in this disease, on the basis of experimental (Rier et al 1993) and etiologic evidence (Bois and Eskenazi 1994;Mayani et al 1997;Eskenazi et al 2000).…”
Section: Introductionmentioning
confidence: 99%
“…early pregnancy loss), and premature reproductive senescence. The need to consider fecundity end-points is supported by a possible relation between PCB exposure and endometriosis (Mayani et al, 1997;Buck Louis et al, 2004) and between consumption of PCB-contaminated fish and diminished fecundability (Axom et al, 2000;Buck et al, 2000). Male fecundity impairments have been associated with both birth defects and chronic disease.…”
Section: Human Studiesmentioning
confidence: 99%